2020
DOI: 10.1097/qai.0000000000002506
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of PrEP Retention Among HIV Pre-exposure Prophylaxis Users in Baltimore City, Maryland

Abstract: Background: HIV pre-exposure prophylaxis (PrEP) retention, defined as quarterly clinical evaluation, is critical to reducing HIV incidence. Our objectives were to determine: (1) visit- and individual-level PrEP retention patterns; (2) and individual-level characteristics associated with low-level PrEP retention 12 months after initiation among PrEP users in Baltimore City, Maryland. Methods: Information was abstracted from medical records among individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“… 40 One reason for the difference could be that sex work is legal and regulated by policy in Senegal (as opposed to the situation in Tanzania and Kenya), 41 and this could have positive implications for the will to seek and remain in health services. Our findings underscore the considerable challenge of poor retention in PrEP services that has been reported elsewhere 42 , 43 and calls for more and better strategies to support retention in PrEP services.…”
Section: Discussionsupporting
confidence: 62%
“… 40 One reason for the difference could be that sex work is legal and regulated by policy in Senegal (as opposed to the situation in Tanzania and Kenya), 41 and this could have positive implications for the will to seek and remain in health services. Our findings underscore the considerable challenge of poor retention in PrEP services that has been reported elsewhere 42 , 43 and calls for more and better strategies to support retention in PrEP services.…”
Section: Discussionsupporting
confidence: 62%
“…However, the present study looked back on the [4] retention rate criteria and discovered that, young females who were not retained in PrEP would have been considered retained in care if the criteria was used, which is not a true reflection in a real life setting as per the PrEP guidelines. Wu et al [23] concurred and stated that, PrEP must be taken for at least twenty-eight (28) days uninterruptedly following the last high risk HIV exposure to receive the maximum protection from PrEP, this implies that when one interrupt the 28 days of taking PrEP pill, it reduces the level of protection to acquire HIV.…”
Section: Prep Retentionmentioning
confidence: 99%
“…36 A study that evaluated PrEP programs in 3 mid-size US cities found that only 30% of patients prescribed PrEP continued to receive PrEP follow-up 12 months later, and an analysis of PrEP users in 7 clinical sites in Baltimore City, MO, found that PrEP retention was 41% at 12 months. 37,38 In contrast, a study of PrEP provided through a community-based clinic serving MSM in San Francisco reported that only 38% of patients had discontinued PrEP within 13 months, 39 and an online study of MSM in WA State reported 80% retention at 1 year. 40 In a prior report from our SHC evaluating data from 2014 to 2016, 40% of patients who started PrEP discontinued it at least once within a year.…”
Section: Discussionmentioning
confidence: 99%